Failure analysis and structural optimization of rubber core and support rib of full-size spherical blowout preventer. (January 2023) - Liu, Yang; Qian, Liqin; Xia, Chengyu; Zou, Jiayan; Lian, Zhanghua; Yi, Xianzhong
Highlights: The optimum constitutive relation data of rubber core were obtained. Obtain real calculation results through the simulation calculation of rubber core. The secondary optimization design of the rubber core structure is studied. The superiority of the improved structure is verified by the test and application. Abstract: In order to reduce the failure of the spherical blowout preventer, the basic calculation formula of the sealing geometric parameters of the spherical blowout preventer are deduced combined with the existing structure and working principle of the spherical blowout preventer in this paper. Based on the test data of four constitutive relationships of rubber core material, the constitutive relationship of rubber core material is obtained by optimizing the four kinds of test data. And this paper studies the deformation law, stress distribution and sealing performance of the rubber core by using finite element software, and finds out the internal of failure causes of the spherical rubber core. The calculation results show that the stress concentration is obvious at the bottom of the rubber core, which is one of the main reasons for the falling off of the rubber rings. The stress values of the neck and back of the support rib are high, which is easy to cause the support rib to bend and break along the neck and back. The indoor test shows that the designed rubber core structure meets the pressure test requirements, and the appearance of the annular rubber core is intact after used in the field. It shows that the optimized structure is helpful to improve the service life of the spherical rubber core.